"Swap" Covered Interest Parity in Long-Date Capital Markets - Fletcher, Donna J.; Taylor, Larry W. (The Review of Economics and Statistics, 1996)
Using the currency swap as the forward-exchange risk hedge, the covered interest parity condition in the long-date capital markets is evaluated. Of interest is the extent to which deviations from parity can be attributed to transactions costs. The empirical conclusions presented in the paper suggest that, although (on average) transactions costs account for deviations from parity, net deviations (in excess of transactions costs) are neither rare nor short-lived. Yet an analysis of the variance structure of covered interest parity reveals that these profit opportunities diminish over time and eventually disappear. Copyright 1996 by MIT Press.